Assessment of P-glycoprotein gene expression in adult stage of Haemonchus contortus in vivo exposed to ivermectin - Maté, María Laura (2018)
The efflux transporter P-glycoprotein (P-gp) has been implicated in multidrug resistance of different nematode parasites affecting livestock species. Increased expression of P-gp in nematodes after their in vitro as well as in vivo exposure to anthelmintics suggests a role of P-gp in drug resistance. The current study evaluated the P-gp gene expression in a highly-resistant isolate of the sheep nematode Haemonchus contortus, selected after exposure to ivermectin (IVM) treatments at 10-fold the therapeutic dose. Four lambs were artificially infected with L 3 (7000 L 3 /animal) of a previously selected IVM highly resistant H. contortus isolate. Forty five (45) days after infection, adult worms were collected at 0 (untreated), 6, 12 and 24 h post-oral IVM (2 mg/kg) administration. The relative transcription levels of different H. contortus P-gp genes were studied by quantitative real-time PCR (qPCR) and confirmed by RNA-seq. P-gp1 and P-gp11 gene expressions did not change throughout the experimental sampling period. P-gp3 and P-gp9.1 transcripts decreased significantly at both 12 and 24 h post IVM exposure. P-gp2 expression was progressively increased in a time-dependent manner at 1.81 (6 h), 2.08 (12 h) and 2.49 (24 h)-fold compared to adult worms not exposed (control 0 h) to IVM, although without reaching statistically significant differences (P > 0.05). P-gp12 was neither detected by qPCR nor by RNA-seq analysis. These relatively modest changes in the P-gp gene expression could not be enough to explain the high level of IVM resistance displayed by the H. contortus isolate under assessment. Overexpression of membrane drug transporters including P-gp has been associated with IVM resistance in different nematode parasites. However, some evidences suggest that resistance to IVM and other macrocyclic lactones may develop by multiple mechanisms. Further studies are needed to improve the understanding of resistance mechanisms in adult stages of H. contortus.